Comprehensive scoping review on adherence to 24-hour movement guidelines and socioeconomic indicators in children and adolescents - Letícia Gonçalves; Suellem Zanlorenci; Melquesedek Ferreira Da Silva Almeida; Jérémy Vanhelst; Diego Augusto Santos Silva (PLoS ONE, 2025)
Background Adherence to the 24-hour movement behavior guidelines has been used to identify potential impacts on health indicators in children and adolescents. However, information on the association between socioeconomic indicators and adherence to the guidelines remains unclear. Objective The scoping review aims to identify and synthesize scientific evidence on the associations between socioeconomic indicators and adherence to the 24-hour movement behavior guidelines in children and adolescents. Methods A systematic search was conducted in PubMed, Web of Science, Scopus, SPORTDiscus, SciELO, CINAHL, and EMBASE. Studies were selected if they included a population of children and adolescents aged 5–17 years and addressed the relationship between adherence to the 24-hour movement behavior guidelines and socioeconomic indicators. Results From 1,871 articles identified, 10 studies with data from 562,505 children and adolescents across 10 countries were included. Self-reported questionnaires were the most common measurement method for variables related to the 24-hour movement behaviors (n=6). The Canadian 24-Hour Movement Guidelines were the most frequently used reference for classifying target behaviors (n=4). Socioeconomic indicators at the individual and/or family level were used in most investigations, specifically parental education (n=7) and household income (n=6). Most findings were inconclusive regarding the relationship between adherence to the 24-hour movement behavior guidelines and socioeconomic indicators. Conclusions Studies on this interrelation have been limited, with inconclusive results regarding associations between socioeconomic indicators and adherence to the 24-hour movement behavior guidelines in children and adolescents. Further research is needed to better understand these relationships.